1984
DOI: 10.1084/jem.159.3.828
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of human interferon-gamma with lymphotoxin and monocyte cytotoxin.

Abstract: Crude preparations of interferon (IFN)-gamma derived from human peripheral blood leukocyte (PBL) cultures induced with 12-O-tetra-decanoylphorbol-13-acetate (TPA) and phytohemagglutinin (PHA) were more cytotoxic to HeLa cells than partially purified nautral or highly purified recombinant human IFN-gamma preparations. Conditioned media from PBL cultures contained, in addition to IFN-gamma, a mixture of cytotoxins, including classic lymphocyte-derived lymphotoxin (LT), and a TPA-induced cytotoxic activity produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
2
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(67 citation statements)
references
References 33 publications
4
59
2
2
Order By: Relevance
“…(rBoIFN-~, rPoIFN-v and rBoTNF-c0. Synergistic activities resulting from mixtures of IFN-v and other IFN types have been described for antiviral activity (Domke et al, 1985) or cell growth inhibition (Czarniecki et aL, 1984;Fleischmann, 1982) and IFN-v synergizes with TNF for induction of activated macrophages (Esparza et al, 1987), cytotoxic activity (Stone-Wolff et al, 1984), differentiation of human myeloid cell lines (Trinchieri et al, 1986) or antiviral activity (Wong & Goeddel, 1986). However, our results indicate that the cytokines used had no synergism as antiviral agents against ASF virus.…”
Section: Discussioncontrasting
confidence: 54%
“…(rBoIFN-~, rPoIFN-v and rBoTNF-c0. Synergistic activities resulting from mixtures of IFN-v and other IFN types have been described for antiviral activity (Domke et al, 1985) or cell growth inhibition (Czarniecki et aL, 1984;Fleischmann, 1982) and IFN-v synergizes with TNF for induction of activated macrophages (Esparza et al, 1987), cytotoxic activity (Stone-Wolff et al, 1984), differentiation of human myeloid cell lines (Trinchieri et al, 1986) or antiviral activity (Wong & Goeddel, 1986). However, our results indicate that the cytokines used had no synergism as antiviral agents against ASF virus.…”
Section: Discussioncontrasting
confidence: 54%
“…Although much is known about TNF-a, very little is understood about TNF-b (Aggarwal, 2003;Aggarwal et al, 2012). Both overlapping and nonoverlapping activities of the two molecules have been reviewed (Stone-Wolff et al, 1984;Kuprash et al, 2002;Liepinsh et al, 2006).…”
Section: Discovery Of Tnfsmentioning
confidence: 99%
“…Cytokines have pleiotropic effects (Sporn & Roberts, 1988) : IFN-y and TNF-a have been shown to play a role in vitro in the induction of class I1 MHC molecules on thyroid cells (Todd et al, 1988). They also have effects on other aspects of thyroid cell physiology since TNF-a has been reported to be one of the essential mediators of antibody-dependent cytotoxicity (ADCC) (Kondo et al, 1981) and cell killing by natural killer (NK) cells (Degliantoni et al, 1986) .This cytokine acts synergistically with IFN-y (Lee et al, 1984;Tsujimoto et al, 1986;Ruggiero et al, 1986;Taverne et al, 1987), which has also been shown to be cytotoxic (Stone-Wolff et al, 1984) and to increase expression of TNF receptors on the surface of tumour cells (Tsujimoto et al, 1986;Ruggiero et al, 1986). On the other hand, IFN-y has been reported to be secreted by lymphocytes isolated from peripheral blood (PB) (Hovdenes et al, 1989;Matsubayashi et al, 1990) or thyroid gland (Karlsson et al, 1986;Sat0 et al, 1993).…”
mentioning
confidence: 99%